2014
DOI: 10.1021/cg500573e
|View full text |Cite
|
Sign up to set email alerts
|

Surface Mediated Structures: Stabilization of Metastable Polymorphs on the Example of Paracetamol

Abstract: The preparation of typically thermodynamically unstable polymorphic structures is a challenge. However, solid surfaces are well established aids for the formation and stabilization of polymorphic structures within, for instance, organic electronics. In this study, we report the stabilization of a pharmaceutically relevant substance via a solid surface at ambient conditions. Form III of paracetamol, which is typically unstable in the bulk at standard conditions, can be stabilized with a model silica surface by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 30 publications
4
68
0
Order By: Relevance
“…Delmas et al Have reported selective crystallization of the orthorhombic form II of PCM using mesoporous silica particles (Delmas et al, ). Similar experiments were also conducted by Ehmann et al with a spin coating of PCM followed by rapid heat treatment in presence of colloidal silica particles (Ehmann & Werzer, ). They have reported crystallization of the polymorphic form III of the PCM which is unstable at ambient conditions.…”
Section: Pharmaceutical Applicationssupporting
confidence: 59%
See 2 more Smart Citations
“…Delmas et al Have reported selective crystallization of the orthorhombic form II of PCM using mesoporous silica particles (Delmas et al, ). Similar experiments were also conducted by Ehmann et al with a spin coating of PCM followed by rapid heat treatment in presence of colloidal silica particles (Ehmann & Werzer, ). They have reported crystallization of the polymorphic form III of the PCM which is unstable at ambient conditions.…”
Section: Pharmaceutical Applicationssupporting
confidence: 59%
“…As per general convention, the metastable form should be stable enough to provide biopharmaceutical advantage upto the shelf life of the product (Singhal & Curatolo, 2004 (Delmas et al, 2013). Similar experiments were also conducted by Ehmann et al with a spin coating of PCM followed by rapid heat treatment in presence of colloidal silica particles (Ehmann & Werzer, 2014). They have reported crystallization of the polymorphic form III of the PCM which is unstable at ambient conditions.…”
Section: Metastable Polymorphsmentioning
confidence: 58%
See 1 more Smart Citation
“…The appearance of new polymorphs of a material, if crystallized at a solid substrate surface, can have a significant impact on the physical properties of the material and, therefore, on any potential applications . Such polymorphs, termed as thin‐film, surface‐mediated, or substrate‐induced phases (SIPs), have mostly been observed for organic semiconductors, but could also be of importance for other classes of molecules, such as pharmaceuticals . These crystal forms are of particular interest because they often show an enhancement of certain properties compared with those of their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Such polymorphs, termeda st hinfilm, surface-mediated, or substrate-induced phases (SIPs), [3] have mostly been observed for organic semiconductors, but could also be of importance for other classes of molecules, such as pharmaceuticals. [4,5] These crystal forms are of particular interest because they often showa nenhancement of certain properties compared with those of their bulk counterparts. For example, the well-known thin-film phase of the organic semiconductor pentacene has better charge-carrier mobility properties than those of the two known bulk polymorphs.…”
Section: Introductionmentioning
confidence: 99%